COVID-19 and prepandemic all-cause inequalities in disability-adjusted life-years due to multiple deprivation: a Scottish Burden of Disease study. (November 2021) - Wyper, Grant M A; Fletcher, Eilidh; Grant, Ian; Harding, Oliver; de Haro Moro, Maria Teresa; Stockton, Diane L; McCartney, Gerry
Abstract: Background: COVID-19 has caused major social, environmental, and economic changes. The mechanisms that shape health inequalities have resulted in COVID-19 outcomes following the same pattern. We aimed to estimate overall, and inequalities in, COVID-19 disability-adjusted life-years (DALYs) in Scotland during 2020. These were scaled against prepandemic DALYs due to inequalities in multiple deprivation combined across all causes. Methods: DALYs were estimated with an international consensus model with Scottish national deaths and daily cases as data inputs. Health loss valuation was defined with the aspirational reference life table and disability weights from the Global Burden of Disease Study 2019. Years of life lost were estimated for each area-based deprivation quintile of the Scottish population. Years lived with disability were distributed to deprivation quintiles, based on the distribution of estimates of years of life lost. Inequalities in rates were measured by the relative index of inequality (RII); slope index of inequality (SII); and attributable DALYs, with the least deprived quintile as a reference category. Prepandemic estimates were for 2018, derived from the Scottish Burden of Disease study. Permissions were granted by the Privacy Advisory Committee, National Health Service, National Services Scotland. Findings: Marked inequalities were observed across several measures in 2020 (Jan 1 to Dec 31). The SII was 2048–2289 COVID-19 DALYs per 100 000 people. The COVID-19 DALYs rate in the most deprived areas (2748–3067 per 100 000 people) was around 58% higher than the mean population rate (RII=1·16), with 40% (n=38 925–43 284) of COVID-19 DALYs attributed to inequalities in multiple deprivation. In the wider context, overall COVID-19 DALYs (n=96 519–108 243) were approximately a fifth of the annual prepandemic DALYs (n=535 298) attributable to inequalities in multiple deprivation. Interpretation: The impact of COVID-19 in Scotland was not shared equally across areas experiencing different levels of deprivation. The extent of COVID-19 inequality was similar to annual DALYs due to diabetes. Implementing effective policy interventions to reduce health inequalities must be at the forefront of plans to recover and improve population health. Communicating the effect of pre-existing inequalities by scaling against COVID-19 could be a useful means to retaining, and increasing, both policy and public engagement and response over tackling inequality. Funding: None.